Diffusion weighted imaging and apparent diffusion coefficient discrimination of odontogenic keratocyst - Pinto, Antonione Santos Bezerra; Sousa, André Luca Araújo de; Falcão, Carlos Alberto Monteiro; Ferraz, Maria Ângela Arêa Leão; Gomes, João Pedro Perez; Lopes, Sérgio Lúcio P. de Castro; Silva, Paulo Henrique Braz da; Costa, André Luiz Ferreira; Cardoso, Luana Leal Cosmo (Journal of Oral Diagnosis, 2023)
Radiological diagnosis of Odontogenic Keratocyst (OKC) is particularly challenging due to its radiological similarities in comparison to other odontogenic lesions. This study aimed to provide data from the literature review and to present a case report in which the diffusion-weighted imaging (DWI) and the apparent diffusion coefficient (ADC) using magnetic resonance imaging (MRI) were obtained to establish a possible way to differentiate OKC from other odontogenic lesions. Literature review data and its association with the present case report shows the potential to use DWI and ADC combination as a possible tool to differentiate OKC from ameloblastomas.